B cell memory to a serogroup C meningococcal conjugate vaccine in childhood and response to booster: little association with serum IgG antibody. - Perrett, K; Jin, C; Clutterbuck, E; John, T; Winter, A; Kibwana, E; Yu, L; Curtis, N; Pollard, A (2012)
The maintenance of adequate serum Ab levels following immunization has been identified as the most important mechanism for individual long-term protection against rapidly invading encapsulated bacteria. The mechanisms for maintaining adequate serum Ab levels and the relationship between Ag-specific memory B cells and Ab at steady state are poorly understood. We measured the frequency of circulating serogroup C meningococcal (MenC)-specific memory B cells in 250 healthy 6- to 12-y-old children 6 y following MenC conjugate vaccine priming, before a booster of a combined Haemophilus influenzae type b-MenC conjugate vaccine and then 1 wk, 1 mo, and 1 y after the booster. We investigated the relationship between circulating MenC-specific memory B cell frequencies and Ab at baseline and following the booster vaccine. We found very low frequencies of circulating MenC-specific memory B cells at steady state in primary school-aged children and little association with MenC IgG Ab levels. Following vaccination, there were robust memory B cell booster responses that, unlike Ab levels, were not dependent on age at priming with MenC. Measurement of B cell memory in peripheral blood does not predict steady state Ab levels nor the capacity to respond to a booster dose of MenC Ag.